Bracing cold-formed steel structures a design guide - Sputo, Thomas; Turner, Jennifer L. (American Society of Civil Engineers, 2006)
"Bracing Cold-Formed Steel Structures: A Design Guide documents the current practices related to bracing cold-formed steel structure elements and systems. Many engineers see the design of structures using cold-formed steels as a daunting task. This report seeks to remove some of the perceived mystery by providing readily useful information for bracing these structures. Heavy on applications and examples, this book contains design examples illustrating bracing design for various types of cold-formed steel structures, as well as an extensive list of primary reference sources. This report is presented as a design guide and will assist the practicing engineer in designing cold-formed steel structures with greater levels of reliability, safety, and economy."--Jacket.
Keywords: Building, Iron and steel.; Steel, Structural.; Steel -- Cold working.; elektronické knihy; electronic books